Radiosensitivitas Pisang cv. Ampyang dan Potensi Penggunaan Iradiasi Gamma untuk Induksi Varian - Indrayanti, Reni (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2017)
Banana is commonly propagated vegetatively by suckers since most of edible banana are triploid, male sterile and parthenocarpic, use of conventional breeding for banana improvement is diffi cult. Mutation induction and in vitro technique are alternative tools for banana improvement. The objectives of this research were (1) to determine radiosensitivity of banana cv. Ampyang against gamma irradiation, and (2) to evaluate performance of plantlets regenerated from gamma irradiated explants of banana cv. Ampyang. Explants of in vitro grown shoots were exposed to gamma irradiation at 0, 20, 25, 30, 35, 40, 45, and 50 Gy to determine their radiosensitivity. Growth and development of regenerated plantlets were recorded after 10 months of proliferation and regeneration periods. The CurveExpert ver. 1.4 analysis results indicated that lethal doses of irradiation reducing 20% to 50% of shoot growth (LD20-50) were 51.07 - 64.54 Gy. All regenerated plantlets from irradiated explants produced less numbers of roots, and some of regenerated plantlets, showed signifi cantly less plantlet fresh weight and height than the control one. Plantlets regenerated from explants irradiated with 25, 40, 50 Gy have longer leaves than the control. The regenerated plantlets from gamma irradiation treatments were successfully transferred into soil and they would be used to evaluate existence of variants among regenerated banana plantlets. Keywords: induced mutation, gamma irradiation, lethal dose (LD20-50)